A prospective study of drug utilization in patients attending ophthalmology outpatient department at KBN teaching and general hospital of Gulbarga, India - Ahmed, Md Mohsin; Harsoor, Amogh; Nizami, Sana (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Drug utilization studies are an important part of rational use of drugs. Assessment of drug use pattern especially in developing countries is becoming increasingly necessary to promote the rational use of drugs. This study was planned to prospectively assess the drug utilization pattern in Ophthalmology outpatient department at KBN teaching and General hospital. Methods: After approval from Ethics Committee, the prescriptions of 1000 outpatients were analyzed using a predesigned form to record information from the OPD prescriptions. Mentioned WHO drug use indicators and additional indices were analyzed: Average number of drugs per prescription, number of encounters with antibiotics, percentage of encounters with injections, percentage of drugs prescribed by their generic names, percentage of drugs prescribed from the National Essential Drug List (NEDL), etc. Results: Prescription analysis showed that the average number of drugs per prescription was 2.6. The drugs were prescribed in the several forms, predominant dosage form been topical eye drops (69.58%) followed by tablets (11.98%), ointments (10.17%) and capsules (6.6%). The ‘dosage form’ was indicated for all of the drugs prescribed, the ‘frequency’ of drug administration was present in 96.5% of the drugs, and the duration of treatment for 82% of the drugs prescribed. Topical Antimicrobial agents were the most commonly prescribed drugs. followed by anti-inflammatory and anti-allergic, lubricants, anti-glaucoma drugs, etc. Percentage of drugs prescribed by generic name and from NEDL was 7.98% and 55 % respectively. Conclusions: The prescription writing errors were less, however, there was very low generic prescribing and inadequate information about the duration of therapy in many prescriptions. Generic prescribing can be improved. Duration of therapy should be mentioned in all prescriptions. It is essential that appropriate guidelines on the use of topical antimicrobials are required to ensure rational prescribing.